Study on Lying Behavior of Learners at the Integrated Islamic Elementary School (SDIT) Darul Ihsan Pontianak - Wicaksono, Luhur; Izdihar, Rafa; Halida, Halida; Alkautsar, Mohamad Abraham; Novita, Shinta (research, training and philanthropy institution Natural Aceh, 2024)
This study aims to determine and describe the lying behavior of students in SD Islam Terpadu Darul Ihsan Pontianak. The subjects of this study consisted of 2 students of Class IV and Class V and six supporting subjects, namely two classmates, two class teachers, and two parents of the subject. This study uses a qualitative approach with descriptive methods. The type of research used is an intrinsic case study, using data collection techniques such as semi-structured interviews and observation. Data analysis using an interactive model includes data reduction, presentation, and conclusion. The results showed that the factors causing students to lie were parental care, relationships with family, social environment, and use of social media. The impact is the loss of trust from people around, the habit of repeated lying behavior, the burden of protracted thoughts, and the damage to social relationships between people. Efforts made by class teachers to overcome lying behavior in students are to provide teaching with integrity about the dangers of lying behavior and manners, provide punishment in the form of reflection to students, become an example that reflects the positive impact of honesty and cooperation with the parents of the students concerned.